2021
DOI: 10.1111/aji.13398
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomics‐determined chemokine‐cytokine pathway presents a common pathogenic mechanism in pregnancy loss and spontaneous preterm birth

Abstract: Problem: Various etiological factors, such as infection and inflammation, may induce the adverse outcomes of pregnancy of miscarriage, stillbirth, or preterm birth. The pathogenic mechanisms associated with these adverse pregnancies are yet unclear.We hypothesized that a common pathogenic mechanism may underlie variant adverse outcomes of pregnancy, which are induced by genetic-environmental factors. The specific objective of the current study is to uncover the common molecular mechanism(s) by identifying the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 63 publications
0
14
0
Order By: Relevance
“…EPL has been grouped into three main categories according to causative factors: 1) resulting primarily from villous maldevelopment (such as in aneuploidy and/or lethal fetal anomalies), 2) resulting mainly from abnormal CTB invasion (such as in the antiphospholipid antibody syndrome), and 3) resulting from the abnormalities at the uteroplacental interface (such as in luteal phase deficiency or chronic inflammatory reaction) [ 59 ]. Among these three categories, EPL is increasingly considered a placentation disorder, resulting from placental oxidative stress, which may cause a thinner and fragmented trophoblast shell, reduced cytotrophoblast invasion of the endometrium and incomplete plugging of the lumen at the tips of the spiral arteries, and premature onset of the maternal circulation and loss of periphery-center coordination, with blood flow occurring throughout the placenta.…”
Section: Discussionmentioning
confidence: 99%
“…EPL has been grouped into three main categories according to causative factors: 1) resulting primarily from villous maldevelopment (such as in aneuploidy and/or lethal fetal anomalies), 2) resulting mainly from abnormal CTB invasion (such as in the antiphospholipid antibody syndrome), and 3) resulting from the abnormalities at the uteroplacental interface (such as in luteal phase deficiency or chronic inflammatory reaction) [ 59 ]. Among these three categories, EPL is increasingly considered a placentation disorder, resulting from placental oxidative stress, which may cause a thinner and fragmented trophoblast shell, reduced cytotrophoblast invasion of the endometrium and incomplete plugging of the lumen at the tips of the spiral arteries, and premature onset of the maternal circulation and loss of periphery-center coordination, with blood flow occurring throughout the placenta.…”
Section: Discussionmentioning
confidence: 99%
“…IL-1b, TNF-a) to activate inflammatory signaling pathways (e.g. NF-kB) in various tissues and organs throughout the body as well as a full range of complement proteins to amplify the inflammatory effects, while infiltrating maternal-fetal interface tissues across the vascular wall under the stimulation of chemokines, causing progressively increasing inflammatory damage and thus leading to PTB (30,(60)(61)(62)(63)(64)(65). Coincidentally, we found that PTB-related DECs in monocytes were mainly involved in this complex series of immune-inflammatory responses, including NF-kappa B signaling pathway, complement receptor-mediated signaling pathway, chemokine receptor activity, and interleukin signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a prospective immunohistochemical analysis of 203 chorionic villus sampling specimens showed that the scores of syndecan-1, a regulator of chemokine function, are correlated with PTB (Schmedt et al, 2012). Recently, a transcriptomic analysis has also reported that the chemokine pathway may present a common pathogenic mechanism in spontaneous PTB (Wang et al, 2021). Taken together, these studies implied that chemokines play important roles in the pathological mechanism of PTB.…”
Section: Preterm Birthmentioning
confidence: 98%
“…RSA is defined as two or more times consecutive miscarriages before 20 weeks of gestation and impacts approximately 5% of childbearing-age women (Pereza et al, 2017; Practice Committee of the American Society for Reproductive Medicine, 2020). A recent transcriptomic analysis proposed chemokines as a common pathogenic mechanism in pregnancy loss (Wang et al, 2021). Abnormal secretion of CXCL5 was reported as an early indicator of miscarriage risk (Whitcomb et al, 2007).…”
Section: Recurrent Spontaneous Abortionmentioning
confidence: 99%
See 1 more Smart Citation